International capital movement, trade policy and unemployment - Sugata Marjit (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1991)
This paper builds up a two country model of trade and unemployment allowing for perfect mobility of capital across the borders. Capital moves from the north to the south, which suffers from unemployment. A few basic policies related to lowering of unemployment are discussed. In particular it is shown that larger tariff as well as smaller tax on foreign capital may reduce employment in the south.
Keywords: 330; Kapitalmobilität; Außenwirtschaftspolitik; Theorie der Arbeitslosigkeit; Theorie